Prominent alumni: YB Dato' Sri Hajah Nancy binti Haji Shukri / Enabella Tasha Dennis ... [et al.] - Dennis, Enabella Tasha; Juman, Juliet Cheria; Abdul Khalik, Khairunisa; Nyareng, Rasiba (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Nancy was born on August 5, 1961, in Kuching, Sarawak, hails from Bibi McPherson and Shukri Mahidi as her parents. Her father's lineage comprises Malay and Melanau ancestry, while her mother's heritage encompasses Scottish, Iban, and Chinese roots. Presently residing in Kuching, Sarawak, Nancy is happily married with three children and she is the tenth child among eleven siblings. Following her victory in the 2008 Malaysian general election, She was graduated from Diploma in Public Administration Institute Teknologi Mara (1985), Bachelor's Degree in Law with honors in University Hull United Kingdom and Masters in Executive Business Administration in Ohio University in United State of America.